WordNet based Multilingual Text Categorization - Amine, Bentaallah Mohamed; Mimoun, Malki (INFOCOMP Journal of Computer Science, 2007)
This article is essentially dedicated to the problem of Multilingual Text Categorization, that consists in classifying documents in different languages according to the same classification tree. The proposed approach is based on the idea to spread the utilization of WordNet in Text Categorization towards Multilingual Text Categorization. Experimental results of the bi-lingual classification of the ILO corpus (with the documents in English and Spanish) show that the idea we describe are promising and deserve further investigation.